The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/14651858.cd004529.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone-proguanil for treating uncomplicated Plasmodium falciparum malaria

Abstract: Background The World Health Organization (WHO) in 2015 stated atovaquone‐proguanil can be used in travellers, and is an option in malaria‐endemic areas in combination with artesunate, as an alternative treatment where first‐line artemisinin‐based combination therapy (ACT) is not available or effective. This review is an update of a Cochrane Review undertaken in 2005. Objectives To assess the efficacy and safety of atovaquone‐proguanil (alone and in combination with arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Atovaquone is a well-tolerated antiparasitic drug used in the treatment of parasitic infections [20,31,32]. As a malaria prophylaxis, atovaquone is given in combination with proguanil-chloride (Malarone ® ) which are thought to act synergistically against the malaria parasite [33].…”
Section: Atovaquone and Proguanil Hydrochloride Function Together To Reduce Sars-cov-2 Infectious Particle Productionmentioning
confidence: 99%
“…Atovaquone is a well-tolerated antiparasitic drug used in the treatment of parasitic infections [20,31,32]. As a malaria prophylaxis, atovaquone is given in combination with proguanil-chloride (Malarone ® ) which are thought to act synergistically against the malaria parasite [33].…”
Section: Atovaquone and Proguanil Hydrochloride Function Together To Reduce Sars-cov-2 Infectious Particle Productionmentioning
confidence: 99%
“…ACTs are already generally accepted as the best treatment regimens for uncomplicated Plasmodium falciparum malaria. They are more effective and have fewer adverse effects than other antimalarials such as atovaquone–proguanil, quinine or mefloquine [ 29 , 30 , 31 , 32 ]. The WHO recommends a total of six ACTs, of which countries can select first‐ and second‐line treatment [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proguanil, originally developed as an antimalarial drug [5], has been documented with good anti-proliferative effects [7]. Compared to metformin, another biguanide compound, the effective antitumor concentration of proguanil is considerably low [7], and it has no side effect of lactic acidosis which appears on other biguanide drugs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Proguanil, a member of the biguanide family, was originally developed as an anti-malarial drug [5]. Interestingly, we noticed that some studies reported that proguanil may exert anticancer effects by reducing tumor hypoxia, inducing mitochondrial dysfunction and oxidative stress, and causing DNA damage [6].…”
Section: Introductionmentioning
confidence: 99%